2009
DOI: 10.1371/journal.pone.0007947
|View full text |Cite
|
Sign up to set email alerts
|

Does Simplicity Compromise Accuracy in ACS Risk Prediction? A Retrospective Analysis of the TIMI and GRACE Risk Scores

Abstract: BackgroundThe Thrombolysis in Myocardial Infarction (TIMI) risk scores for Unstable Angina/Non-ST–elevation myocardial infarction (UA/NSTEMI) and ST-elevation myocardial infarction (STEMI) and the Global Registry of Acute Coronary Events (GRACE) risk scores for in-hospital and 6-month mortality are established tools for assessing risk in Acute Coronary Syndrome (ACS) patients. The objective of our study was to compare the discriminative abilities of the TIMI and GRACE risk scores in a broad-spectrum, unselecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 25 publications
2
77
1
12
Order By: Relevance
“…19,20,22, 23 In a prior study in USA to validate the accuracy of GRACE 1.0 for in-hospital mortality in 698 STEMI patients, GRACE 1.0 had a high accuracy on ROC analysis, with an AUC as high as 0.84. 17 Although minor differences were observed in some studies, 22 validation studies have confirmed the accurate predictive ability of GRACE 1.0 for short-term mortality.…”
Section: Discussionmentioning
confidence: 93%
“…19,20,22, 23 In a prior study in USA to validate the accuracy of GRACE 1.0 for in-hospital mortality in 698 STEMI patients, GRACE 1.0 had a high accuracy on ROC analysis, with an AUC as high as 0.84. 17 Although minor differences were observed in some studies, 22 validation studies have confirmed the accurate predictive ability of GRACE 1.0 for short-term mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Skala ryzyka GRACE umożliwia najdokładniejszą ocenę ryzyka zarówno przy przyjęciu, jak i przy wypisaniu ze szpitala [92,93]. Kalkulator ryzyka GRACE 2.0 (http:// www.gracescore.org/WebSite/default.aspx?ReturnUrl=%2f) umożliwia bezpośrednie oszacowanie śmiertelności w trakcie pobytu w szpitalu, po 6 miesiącach, po roku i po 3 latach, z pominięciem oceny za pomocą tradycyjnej skali punktowej.…”
Section: Ocena Ryzyka Niedokrwieniaunclassified
“…The study is limited by the relatively small number of studies included in the review and the statistical heterogeneity between studies, which limits the quality of the evidence and our ability to assess publication bias. Although the Global Registry of Acute Coronary Events (GRACE) risk score has been shown to have greater discriminative ability than the TIMI risk score for mortality in-hospital and at six months in patients with confirmed acute coronary syndromes, 25 few studies have assessed the performance of the GRACE score in emergency department patients with potential acute coronary syndromes. One study reported a sensitivity of 100% and a specificity of 13%, with data needed to calculate a complete GRACE score missing for 24% of patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%